2015
DOI: 10.1371/journal.pone.0133189
|View full text |Cite
|
Sign up to set email alerts
|

Axial Myopia Is Associated with Visual Field Prognosis of Primary Open-Angle Glaucoma

Abstract: PurposeTo identify whether myopia was associated with the visual field (VF) progression of primary open-angle glaucoma (POAG).MethodsA total of 270 eyes of 270 POAG followed up for more than 3 years with ≥9 reliable VFs by Octopus perimetry were retrospectively reviewed. Myopia was divided into: mild myopia (-2.99 diopter [D], 0), moderate myopia (-5.99, 3.00 D), marked myopia (-9.00, -6.00 D) and non-myopia (0 D or more). An annual change in the mean defect (MD) slope >0.22 dB/y and 0.30 dB/y was defined as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Literature shows nonsignificant effect of myopia on NTG,[ 16 , 26 , 27 , 29 , 32 , 34 ] and even protective role in some studies. [ 15 , 16 , 34 , 35 ] Caution is needed in a perspective that the progressive course of myopic NTG might differ from nonmyopic NTG. It has been suggested that RNFL defects in myopia might not progress further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature shows nonsignificant effect of myopia on NTG,[ 16 , 26 , 27 , 29 , 32 , 34 ] and even protective role in some studies. [ 15 , 16 , 34 , 35 ] Caution is needed in a perspective that the progressive course of myopic NTG might differ from nonmyopic NTG. It has been suggested that RNFL defects in myopia might not progress further.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 14 , 37 ] Axial myopia was associated with progression in open-angle glaucoma. [ 15 ] In studies with NTG patients in Japanese population, myopia was a positive factor for glaucoma progression. [ 27 , 34 , 35 ] Meanwhile, there are other studies reporting absence of difference in glaucoma progression between myopic and nonmyopic group.…”
Section: Introductionmentioning
confidence: 99%
“…Although elevated intraocular pressure (IOP) is the most common and the only modifiable risk factor of POAG, there are many other factors that can contribute to optic nerve damage or disease progression. [ 4 8 ] One hypothetical cause may be insufficient ocular blood flow leading to optic nerve ischemia and glaucomatous optic neuropathy. [ 6 , 9 11 ] In animal models, diminished ocular perfusion has been shown to induce retinal ganglion cell loss in spite of a normal IOP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanism of the impact of myopia on VF progression in OAG is still unknown, one possible hypothesis is that the difference of axial length might positively affect IOP fluctuation. 36 , 37 Axial length is one of the major factors contributing to myopia. Loewen et al 38 reported that basal 24-hour habitual IOP fluctuation was negatively correlated with axial length in a comparison of healthy adults with hyperopia, emmetropia, and myopia.…”
Section: Discussionmentioning
confidence: 99%